2017
DOI: 10.1111/tpj.13640
|View full text |Cite
|
Sign up to set email alerts
|

A computational approach for inferring the cell wall properties that govern guard cell dynamics

Abstract: SummaryGuard cells dynamically adjust their shape in order to regulate photosynthetic gas exchange, respiration rates and defend against pathogen entry. Cell shape changes are determined by the interplay of cell wall material properties and turgor pressure. To investigate this relationship between turgor pressure, cell wall properties and cell shape, we focused on kidney‐shaped stomata and developed a biomechanical model of a guard cell pair. Treating the cell wall as a composite of the pectin‐rich cell wall m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 73 publications
2
85
0
Order By: Relevance
“…This would entail an initial turgor-induced change in geometry from elliptical to circular (inflation), followed by an accommodation of any further increase in pressure by cell wall stretching, a process that requires higher turgor differentials to produce visible results. Therefore, the matrix strain-stiffening conjecture proffered by Woolfenden et al (2017), while consistent with polymer chemistry (Bidhendi and Geitmann, 2016), could be a secondary mechanism responsible for the apparent low sensitivity of aperture opening at high pressures. These concepts certainly merit further validation.…”
Section: Reassessing the Contribution Of Cellulose-induced Radial Animentioning
confidence: 77%
See 4 more Smart Citations
“…This would entail an initial turgor-induced change in geometry from elliptical to circular (inflation), followed by an accommodation of any further increase in pressure by cell wall stretching, a process that requires higher turgor differentials to produce visible results. Therefore, the matrix strain-stiffening conjecture proffered by Woolfenden et al (2017), while consistent with polymer chemistry (Bidhendi and Geitmann, 2016), could be a secondary mechanism responsible for the apparent low sensitivity of aperture opening at high pressures. These concepts certainly merit further validation.…”
Section: Reassessing the Contribution Of Cellulose-induced Radial Animentioning
confidence: 77%
“…The role of cellulose orientation and cell wall anisotropy was reassessed in a recent study by Woolfenden et al (2017), who used nonlinear elasticity with a transversely isotropic material behavior to represent the guard cell wall, similar to studies by Cooke et al (1976). The authors observed that, using isotropic material properties, increasing the turgor pressure causes the stomatal pore to close rather than open.…”
Section: Reassessing the Contribution Of Cellulose-induced Radial Animentioning
confidence: 87%
See 3 more Smart Citations